Review of Drug Interactions with Telaprevir and Antiretrovirals. Issue 4 (May 2013) - Van Heeswijk, Rolf PG; Beumont, Maria; Kauffman, Robert S; Garg, Varun
HCV infection is a major cause of mortality worldwide. HCV-related deaths also represent a leading cause of mortality in HIV-coinfected individuals. Telaprevir is an NS3/4A protease inhibitor approved for the treatment of chronic HCV genotype 1 infection in adults in combination with pegylated interferon and ribavirin. Telaprevir-based treatment has been shown to increase rates of sustained viral response in HCV genotype-1-monoinfected patients, and studies in HCV–HIV-coinfected patients are ongoing. Drug–drug interactions of telaprevir with antiretroviral drugs were investigated in a series of studies in healthy subjects. This review summarizes the results of interaction studies with low-dose ritonavir, ritonavir-boosted HIV protease inhibitors (atazanavir, darunavir, fosamprenavir and lopinavir), efavirenz, etravirine, rilpivirine, tenofovir disoproxil fumarate and raltegravir.